PENGARUH PRODUKSI CABAI MERAH (CAPSICUM ANNUM L.) TERHADAP HARGA PENJUALAN DI TINGKAT PETANI - TONNY HENDRA NADEAK (JURNAL ILMIAH KOHESI, 2020)
This study aims to find out the influence of red chili production on the sales price at the farmer level and know theproductivity of red chili in the research area. This research was conducted in Sipituhuta Village, Pollung District,Humbang Hasundutan Regency. The determination of samples was done in simple random sampling with a totalof 31 respondents. Data analysis is done with a simple linear regression test. The results showed that there is anegative relationship between the price and the production of red chili peppers. This means that the higher theselling price of red chili, the lower the production of red chili peppers. The average production of red chili farming is2,770.84 kg / farmer with an average land area of 0.60 hectares, so the average productivity of red chili farming is4,422.17 kg / hectare / mt.